Formation of solids in ammonia-based CO2 capture processes — Identification of criticalities through thermodynamic analysis of the CO2–NH3–H2O system. (8th September 2015) - Sutter, Daniel; Gazzani, Matteo; Mazzotti, Marco
Abstract: The formation of solid intermediate compounds may lead to equipment clogging and plant shutdown in ammonia-based CO2 capture processes. In this work, the thermodynamics of the CO2 –NH3 –H2 O system are analyzed with a focus on solid formation. The critical streams and unit operations that may be concerned with solid formation are identified based on an exemplary process simulation and on ranges of operating conditions typically reached according to the literature. Implications for process design and energy consumption are discussed and ternary phase diagrams mapping the composition regimes of solid formation and the typical operating conditions are presented. Abstract : Graphical abstract: Abstract : Highlights: Phase diagrams visualize the complex thermodynamics of the CO2 –NH3 –H2 O system. Critical streams for solid formation in the CAP are identified. Ranges for typical conditions of critical streams are mapped on phase diagrams. Energetic optimization of CAP pushes critical compositions towards solubility limit. Process design considerations for avoidance of solids are given.